a) 7(x-3)=-42
b) -3(x+1)=2(x+1)-75
c) 2(x-1)=3(x+4)
d) 5(x-2)-7(x+4)=0
e) 5(-x+2)=-4(2x-4)
f)2(x-3)-5(3x+4)=-8x+4
g) -3(-5x+7)+8=4(4x-5)-42
Răspunsuri la întrebare
Răspuns de
1
a) x-3= 6
x=9
b) -3x-3=2x+2-75
-3x-2x=2-75+3
-5x=-70
x= 14
c)2x-2=3x+12
2x-3x=12+2
-1x=14
x=-14
d)5x-10-7x-28=0
5x-7x=0+10+28
-2x=38
x=-19
e)-5x+10=-8x+16
-5x+8x=16-10
3x=6
x=2
f)2x-6-15x-20=-8x+4
2x-15x+8x=4+6+20
-5x=30
x=-6
g)15x-21+8=8x-20-42
15x-8x=-20-42+21-8
7x=-49
x=-7
x=9
b) -3x-3=2x+2-75
-3x-2x=2-75+3
-5x=-70
x= 14
c)2x-2=3x+12
2x-3x=12+2
-1x=14
x=-14
d)5x-10-7x-28=0
5x-7x=0+10+28
-2x=38
x=-19
e)-5x+10=-8x+16
-5x+8x=16-10
3x=6
x=2
f)2x-6-15x-20=-8x+4
2x-15x+8x=4+6+20
-5x=30
x=-6
g)15x-21+8=8x-20-42
15x-8x=-20-42+21-8
7x=-49
x=-7
lauraciortan:
Mersi
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Studii sociale,
8 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă